Decolonized Research-Storying Bringing Indigenous Ontologies and Care into the Practices of Research Writing - Kramvig, Britt; Guttorm, Hanna Ellen; Kantonen, Lea; Pyhälä, Aili (Brill, 2021)
In this chapter we want to bring Indigenous ontologies and ways of knowing into the practices of decolonized research-storying. One implication about that is bringing Eana, Earth in North Sámi, as a narrator into the text. This text is a collaborative endeavour, where we write about and with our encountering and living with/in Indigenous societies and ontologies. Care becomes present both in creating space for Indigenous ontologies in research-storying and in sharing and inviting other researchers to share their stories of friction in order to make the ontological change more likely to happen.